A Finite Element Analysis of Dissimilar Materials Diffusion Bonded Joints. (2018) - Deepak, P.; Latheesh, V.M.; Sumesh, A.; Unnikrishnan, D.; Santhakumari, A.
Abstract: Diffusion bonding is one of the solid state joining process, in which two clean metallic surfaces intended for joining were brought into contact at elevated temperatures under optimum pressure. In this work, an attempt is made to study the analysis and simulation of the two dissimilar materials Titanium alloy (Ti-6Al-4V) and Stainless Steel (SS304) which is having a wide application in the area of aerospace. Structural analysis was carried out to determine the equivalent stress, elongation and total deformation of the welded joint. Explicit Dynamics analysis using Ansys was used to predict the strength of Ti-6Al-4V/SS304 diffusion bonded joint. The result indicates that Equivalent stress is attained at 1.393GPa and total deformation is 0.00275m obtained at a time 0.000041seconds. The analysis shows that the fracture occurs in the region of titanium alloy and not in the region of HAZ.